Academic Socialization From an "Informed Distance": Low-Income Chinese American Adolescents' Perceptions of Their Immigrant Parents' Educational Messages. Issue 4 (April 2022) - Bempechat, Janine; Cheung, Amy; Li, Jin
Background/Context: Despite research that has rebutted the tiger parent stereotype, the perception that Asian immigrant parents enact overly strict and controlling educational practices continues to be widespread and entrenched. This stereotype is problematic because it constrains the understanding of Asian Americans to a one-dimensional group and engenders a false narrative of Asian American educational success as expected. Purpose/Objective/Research Question/Focus of Study: Using an intersectional lens, this study interrogates the stereotype of Asian immigrant parents as tiger parents. We examine how one subgroup of Asian American youth—lower income Chinese American adolescents (children of Chinese immigrants) spoke about their parents' involvement in their schooling and educational expectations. Our aim is to center young people's explanations to explore how they perceive parental educational socialization and whether it conforms to notions of tiger parenting. We posed the following three specific research questions: (1) How do these students speak about and understand the ways in which their parents monitor their schoolwork? (2) How do these students describe and understand their parents' messaging of educational expectations? and (3) In what ways do these students depict parent–child communication in their families? Research Design: Participants were 32 ninth-grade low-income Chinese American children of immigrants. We conducted individual interviews focused on educational socialization in the home. We used a combination of inductive and theoretically driven thematic analysis and explored the extent to which students' perspectives of their parents converged or diverged with the tiger parent stereotype. We adopted a working definition of tiger parenting based on categories related to parenting, including close monitoring of schoolwork, perceptions of high parent expectations for school performance and educational/career attainment, and parent-initiated communications regarding children's academic lives and decisions. Findings/Results: Our analysis revealed that participants did not experience their parents' educational involvement as conforming to the tiger parent stereotype. Instead, students were largely self-directed and described their parents as exercising basic monitoring of schoolwork, conveying generic and pragmatic educational and career expectations, and trusting their children overall to manage schoolwork and share key school-related information as needed. We introduce a concept that we call "informed distance" as more salient for understanding our participants' experiences. Conclusions/Recommendations: Educators must interrupt the tiger parent and model minority stereotypes to make room for a fuller and more complex understanding of Asian American students' experiences and ensure their educational needs are equitably addressed. Teachers and counselors can play an affirmative role in educational guidance for Chinese American students.